Penerapan Pencahayaan Pada Animasi Tiga Dimensi Teater Merah Putih Untuk Mengatur Dinamika Dan Kualitas Gambar Animasi - Hellik Hermawan; Ilham Albana; Anggit Bintang Prasetyo; Deden Deden (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The creation of the animation "Red and White Theater" uses an open-source 3D application called Blender 3D with version 2.83 and uses the EEVEE rendering engine that is already available in the Blender 3D application. Rendering in the Red and White Theater animated scene is still far from expected in terms of visuals, due to the time rendering of the animation is very time-consuming. The problem caused by not optimally an animated file/scene is a long work time when opening the scene for the first time, and feels heavy when navigating the scene. The solution to the problem is to remake the animation "Red and White Theater" by changing the lighting side which will have an impact on the addition of visual aesthetics and optimal lighting. The purpose of this research is to change the old light method in order to cut rendering time without compromising the quality of the animation. The research method of animation making is divided into 3 stages, namely pre-production, production, and post-production. The result of validation with a percentage for material decay is 79% and lighting manufacturing is 81% which belongs to the interval of the category of excellent assessment based on the results of questionnaires given to 30 respondents.